2021
DOI: 10.32014/2021.2518-170x.32
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of Lead Production Wastes by Extraction of Lead and Zinc Oxides

Abstract: Information is given about the need to dispose of waste from the Shymkent lead plant in the form of slags, which have accumulated about 2 million tons. It is proved that lead production slags contain a large number of toxic compounds, such as lead, zinc, osmium, and cadmium, which are dangerous sources of environmental pollution. According to the results of X-ray diffractometric analysis and DTA, it was found that the slag of lead produc- tion contains a fairly high number of non-ferrous metal compounds: the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…To identify the plumbum residuals' chemical composition, the authors made chemical, thermal, X-ray phase and spectral analyses in Almaty at Institute of Geological Sciences named after K.I. Satpayev and at Institute of Metallurgy and Ore Beneficiation of the National Academy of Sciences of the Republic of Kazakhstan [14].…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the plumbum residuals' chemical composition, the authors made chemical, thermal, X-ray phase and spectral analyses in Almaty at Institute of Geological Sciences named after K.I. Satpayev and at Institute of Metallurgy and Ore Beneficiation of the National Academy of Sciences of the Republic of Kazakhstan [14].…”
Section: Experimental Partmentioning
confidence: 99%
“…The investigation of the sample in the polished briquet in the incident light, exhibited in Figure 1, identified that the slag sample is composed of an amorphous matrix with multiple heterogeneous copper mineral phase inclusions outwardly resembling natural copper sulfide minerals, like native copper and chalcopyrite, that are frequently round and isometric, have typical of chalcopyrite light-yellow color [14,19].…”
Section: Table 4 the Crystalline Phases' Semiquantitative X-ray Phase...mentioning
confidence: 99%
See 1 more Smart Citation